The Coronation of the Diadochi - Erich Stephen Gruen (Universitat Autònoma de Barcelona. Departament de Ciències de l’Antiguitat i l’Edat Mitjana., 2018)
The year 310 B.C. witnessed the extinction of the Argead line. Cassander had ordered the murder of Young Alexander IV and his mother Roxane, widow of Alexander the Great. The kingdom of Macedonia was now without a king. Cassander’s deed cleared the way for the ambitious dynasts who controlled the armies and lands of the eastern Mediterranean. Yet no one stepped forth to claim the crown. The throne lay vacant for four years. In 306 the situation changed in dramatic fashion. Antigonus Monophthalmus took the title of King, and a chain reaction followed. Within a short span of time, Ptolemy, Seleucus, Lysimachus, and Cassander all acquired the same title. The Hellenistic world which had had no monarch for half a decade suddenly had a plethora of them. But what kind of monarchy, how viewed and how justified? The matter is important. It helped give shape to the age of Alexander’s Successors.